Decentralized job scheduling in the cloud based on a spatially generalized "Prisoner`s Dilemma" game - Gąsior, Jakub; Seredyński, Franciszek (Zielona Góra: Uniwersytet Zielonogórski)
We present in this paper a novel distributed solution to a security-aware job scheduling problem in cloud computing infrastructures. We assume that the assignment of the available resources is governed exclusively by the specialized brokers assigned to individual users submitting their jobs to the system. The goal of this scheme is allocating a limited quantity of resources to a specific number of jobs minimizing their execution failure probability and total completion time.
Keywords: job scheduling; multiobjective optimization; genetic algorithms; Prisoner`s Dilemma; cellular automata